ANALYSIS OF THE STUDENTS’ ENGLISH TENSES ERRORS - Eko Setiawan; M. Fadhly Farhy Abbas (Universitas Lancang Kuning, 2018)
At The First Semester of English Students’ Department at Faculty of Teacher Training andEducation LancangKuning University, the researcher found that the students had a problem inhad grammar error in writing. That was why researcher conducted this research that aimedtoanalyze the English errors faced by the first semester of English Students Department atFaculty of Teachers Training and EducationLancangKuning University.This research wasDescriptive Quantitative Research. The participants of the research were 36 students. Incollecting the data in this research, the researcher used test and interview as the instrument. Theresult of data showed that the students had 176 errors in verb tenses, 8 errors in to be, 5 errors incorrect sentence and 9 in adverb of time with the percentage were 31,38 % in true or falsequestion and 27,5 % in multiple choice test. In conclusion, The students had a lot of errors inapplied verb tense, adverb of time, correct sentence, and to be.